2021
DOI: 10.1093/jjco/hyab187
|View full text |Cite
|
Sign up to set email alerts
|

Management of bladder cancer in older patients

Abstract: Evidence has shown that patients with bladder cancer are diagnosed at a much older age compared with those with other cancers. Given that co-morbidities and frailty are prevalent in older patients with advanced bladder cancer, they are easily excluded from randomized controlled trials. As little evidence has been available regarding assessment tools for frailty, the management of those patients remains challenging. This weakness is strongly manifested in muscle-invasive bladder cancer. Despite radical cystecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
6
0
1
Order By: Relevance
“…A sudden change in living environment is a major stress and risk factor for the development of delirium 15,16 . Moreover, standard treatment is not feasible in older patients with frailty because of their considerable comorbidities, frailty, and potential risk of experiencing adverse events 15–23 . In particular, poor prognosis due to undertreatment has also been reported for muscle‐invasive bladder cancer 21–23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sudden change in living environment is a major stress and risk factor for the development of delirium 15,16 . Moreover, standard treatment is not feasible in older patients with frailty because of their considerable comorbidities, frailty, and potential risk of experiencing adverse events 15–23 . In particular, poor prognosis due to undertreatment has also been reported for muscle‐invasive bladder cancer 21–23 .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, standard treatment is not feasible in older patients with frailty because of their considerable comorbidities, frailty, and potential risk of experiencing adverse events. [15][16][17][18][19][20][21][22][23] In particular, poor prognosis due to undertreatment has also been reported for muscle-invasive bladder cancer. [21][22][23] With the increase in the number of older patients, invasive treatment for this population poses a challenge in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most elderly patients pose a substantial challenge to treatment because of the high incidence of complications and frail status. With the aging of society, the number of patients with bladder cancer will also increase and it is noteworthy that cardiovascular disease is a common illness among elderly patients, however a study found that cardiovascular disease was an independent protective factor for bladder cancer, but this effect was not observed in high-risk tumors ( 23 ), therefore, for such high risk tumor, to construct an effective assessment tool can help physicians make better decisions ( 24 ). In our analysis, the best cut-off value of age was obtained by x-tile software and age acted as the predictive factor of prognosis in patients with MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with cancer tend to have greater levels of frailty in comparison to individuals without cancer [ 17 ]. Furthermore, data (albeit limited) suggest that patients with kidney cancer, concurrent cancer with CKD, AKI with cancer, and/or treatment-associated nephrotoxicities most likely have worsened clinical outcomes with increased frailty [ 66 , 70 , 71 , 72 , 73 ]. Considering these factors, frailty status would be useful as a marker to guide clinical decision-making in onconephrology.…”
Section: Clinical Significance Of Frailty Assessment In Onconephrologymentioning
confidence: 99%